ON THE LOCATION OF ZEROS OF QUASI–ORTHOGONAL POLYNOMIALS WITH APPLICATIONS TO SOME REAL SELF–RECIPROCAL POLYNOMIALS - Botta, Vanessa [UNESP]; Suni, Mijael Hancco [UNESP] (Element d.o.o., 2022)
In this paper, we present new results on the location of zeros of some classes of quasi-orthogonal polynomials. From the Chebyshev polynomials, we obtain some classes of real self-reciprocal polynomials, and investigate the location and monotonicity of their zeros.
Keywords: Chebyshev polynomials; Quasi-orthogonal polynomials; self-reciprocal polynomials; symmetric orthogonal polynomials; unit circle; zeros